ЭҲТИМОЛЛАР НАЗАРИЯСИ ВА МАТЕМАТИК СТАТИСТИКА ФАНИНИ ЎҚИТИШНИНГ БАЪЗИ ХУСУСИЯТЛАРИ (Scientific journal of the Fergana State University, 2023)
In this article, some aspects of teaching of probability theory and mathematical statistics are consioled.